Impacto del uso de antibióticos en la agricultura y ganadería sobre la propagación de la resistencia bacteriana en humanos - Lalama Gavilánez, Marcos Stefano (2025)
Antibiotics are a class of compounds, both natural and synthetic, that have the effect of killing or inhibiting bacterial growth in animals, plants and people, but excessive use of antibiotics produces resistance, as an effect of the adaptation of bacteria, managing to evade the effects of antibiotics. The general objective of the research presented is to describe the impact of the use of antibiotics in agriculture and livestock on the spread of bacterial resistance in humans. A systematic review of the scientific literature was carried out to locate and summarize recent publications on definitions and epidemiology using the PRISMA 2020 methodology, selecting 23 documents that were analyzed and whose content was incorporated. It was concluded that the incorrect use of antibiotics in livestock and agriculture that generates products for human consumption has led to the creation of a major problem, reaching the point of identifying its impact as a public health problem that considerably affects people. Therefore, strategies are required to reduce bacterial resistance by applying internal and external protocols and quality controls in agricultural and livestock activities that generate products for human consumption.